EXPLORING THE USE OF AI-BASED APPLICATIONS BY EARLY CHILDHOOD EDUCATION TEACHERS TO ASSIST THE COMPLETION OF TEACHER PROFESSIONAL TASKS - Kristin Anggraini (Magister Scientiae, 2025)
The era of society 5.0 has had a tremendous impact on human life, especially on existing technological developments. The various technologies created can also be utilized in the education sector. One technology that can be utilized in the education sector is artificial intelligence (AI). Rapid technological advances must be balanced with the ability of teachers to recognize and operate this technology. It is hoped that the teacher's ability to recognize and operate technology can transmit knowledge about technology to students. In this way, students have been trained from an early age to be able to face the challenges of future developments. Therefore, researchers aim to conduct research that focuses on the effectiveness of the application of Artificial Intelligence (AI) in learning in early childhood education. This research is a qualitative descriptive study that uses data collection techniques through surveys. Next, all the data collected from the literature review and survey results are analyzed to be described. Based on data taken from one hundred and three teachers, it shows that the introduction and application of AI technology-based applications among early childhood education teachers is still not effective, because there are still many teachers who are not familiar with or have never accessed these various applications. Apart from that, the use of AI-based employee attendance applications is still not implemented optimally, even though the implementation of this application can help detect teacher attendance at school and can increase a teacher's professional competence.